The 1970 eruption on Deception Island (Antarctica): eruptive dynamics and implications for volcanic hazards - Dario Pedrazzi; Gerardo Aguirre-Díaz; Stefania Bartolini; Joan Martí; Adelina Geyer (2016)
In the southern winter of 1970, a phreatomagmatic eruption occurred in the northern part of Deception Island (South Shetland Archipelago, Antarctic Peninsula). The eruption, with no eye-witnesses to the event, occurred in the same general area as the 1967 eruption, but with new, more widely distributed vents. Two contrasting groups of craters were formed in the 1970 eruption, showing that different active fissures and eruptive dynamics were operating. One group consists of ‘maar-like’ craters, whereas the other comprises conical edifices. The 1970 eruption can be classified as volcanic explosivity index (VEI) 3, with mainly phreatomagmatic phases that generated a bulk volume of about 0.1 km 3 of pyroclastic material and an eruptive column at least 10 km high, from which fallout deposits are recognized more than 100 km to the NE. The 1970 eruption was similar to that of 1967 and together these two eruptive events show how eruption dynamics can be controlled by the uppermost part of the volcano substrate and the width and orientation of the eruptive fissure. These influence magma–water interaction and hence may imply different eruptive phases and associated volcanic hazards.